Intervenciones de enfermería en una gestante de 37 semanas con diagnóstico de preeclampsia. - Espín Yánez, Leydy Lisbeth (2021)
Preeclampsia is a pathology of placental origin characterized by: high blood pressure (≥ 140-90 mmHg) from the twentieth week of pregnancy or throughout the puerperium. It is called mild pre-eclampsia once the blood pressure is ≥ 140/90 mmHg, severe pre-eclampsia when the blood pressure ranges between 160/110 mmHg without systemic consequence, and severe pre-eclampsia once the blood pressure is ≥ 160/110 mmHg accompanied by pathologic proteinuria (≥300 mg / day) with evidence of maternal target organ damage or failure (brain, heart, lungs, kidneys, liver, coagulation cascade). The complication of pre-eclampsia is eclampsia determined by the appearance of generalized tonic-clonic seizures in a patient with pre-eclampsia that cannot be explained by a different cause. Above all, the above is of vital importance to recognize the signs and symptoms for the application of a timely treatment, in addition to educating the pregnant woman about the care that she should have before, during and after pregnancy. For this reason, the study of this clinical case of a preeclantic patient admitted to the Baba Basic Hospital is carried out, to which the nursing care process will be applied in order to provide standardized care to improve the patient's condition and avoid irreversible sequelae in the mother and her new self.